An Examination of The Protagonist in Pidi Baiq's Novel Dilan: Dia Adalah Dilanku 1991 - Suparni, Suparni; Ratnaningsih, Ratnaningsih (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2022)
Novels are fictional stories that are created by human reflection on the environment and experiences. Within a novel, the author uses their aesthetic experience and creativity to arrange storylines and characters. Examining the characters within a contemporary novel can be intriguing as the main character may reflect the author's idealism and response to their own life. With this in mind, the researcher analyzes the novel "Dilan dia adalah Dilanku 1991" by Pidi Baiq, which has gained popularity among millennial youth. The novel follows the story of high school sweethearts, Dilan and Milea. The researcher focuses on the main characters, Dilan and Milea, and uses a descriptive qualitative method and content analysis to identify certain characteristics related to their characterizations. The study found that Dilan was a romantic, brave, stubborn yet intelligent male figure, while Milea was a loyal, loving, and firm woman.